2009
DOI: 10.1111/j.1746-1561.2009.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Walking School Bus: Lessons Learned*

Abstract: Effective, low-cost interventions are increasingly desired as solutions to the problem of obesity. The WSB has emerged as a promising strategy to address obesity and encourage partnerships across different social levels. Further research is necessary to assess the logistical challenges associated with conducting a large-scale WSB trial and whether such efforts lead to reductions in obesity risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 12 publications
0
62
0
1
Order By: Relevance
“…• frequent and varied communication strategies, • integration of health promotion into existing school environments and curricula, • a longer planning [29,43] and implementation period, • a health promotion-educated staff member dedicated to the project which would allow a key contact for the school for the wider community, may decrease school staff workload, will provide health promotion knowledge for staff who may not have the skills and confidence in this area, and provides resources and support [44], • schools could have their own project officer (with a health promotion background), or a centrally co-ordinated team servicing all schools, or perhaps a mixture of both strategies, • the presence of project officers and their location (e.g. within local government, primary care partnership etc.)…”
Section: Recommendationsmentioning
confidence: 99%
“…• frequent and varied communication strategies, • integration of health promotion into existing school environments and curricula, • a longer planning [29,43] and implementation period, • a health promotion-educated staff member dedicated to the project which would allow a key contact for the school for the wider community, may decrease school staff workload, will provide health promotion knowledge for staff who may not have the skills and confidence in this area, and provides resources and support [44], • schools could have their own project officer (with a health promotion background), or a centrally co-ordinated team servicing all schools, or perhaps a mixture of both strategies, • the presence of project officers and their location (e.g. within local government, primary care partnership etc.)…”
Section: Recommendationsmentioning
confidence: 99%
“…Most of the pilot studies reported in the literature have focused mainly on reporting the results of the pilot trials in terms of outcomes (Williams et al 2007, Kalman et al 2009) and not on the implementation process per se (Van Teijlingen et al 2001, Kong et al 2009) which may also provide valuable insights on the design and operational aspects, as well as readiness for implementing main studies (Lancaster et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many obesity prevention and intervention programs are costly, time consuming and inappropriate for preschool children (Kong et al, 2009;Sahota et al, 2001;Watson et al, 2011). Although some programs found in the literature may be effective, they are not possible for educators and health care professionals to administer in busy settings with tight budgets and time constraints.…”
Section: Significance Of the Studymentioning
confidence: 97%
“…Existing educational programs that target obesity include Walking School Bus (Kong et al, 2009), which encouraged physical activity by requiring its participants to walk to and from school rather than riding the bus. Although effective, this intervention required a great deal of adult supervision in order to keep the participants safe during the walking sessions.…”
Section: Review Of the Literaturementioning
confidence: 99%